PENGEMBANGAN DESTINASI WISATA WARISAN BUDAYA DI DESA BAYAN UNTUK PARIWISATA BERKELANJUTAN - Triutami, Baiq Asri (Tourism, Hospitality And Culture Insights Journal, 2024)
Planning and development of cultural tourism areas is a concrete form of cultural preservation and benefits for the development of good tourism which has the values ​​of preserving cultural assets, so that these cultural assets can function more optimally to increase and understand society about the importance of the nation's cultural works in form of good cultural and tourism management. The challenges faced in cultural development are basically the high level of materialism in society which is starting to abandon the noble values ​​of national culture and the decline in morals in some communities. Therefore, the aim of this research is to analyze the development of cultural heritage tourist destinations in Bayan village for sustainable tourism. The method used is descriptive qualitative research, namely explaining the relationship between the phenomena studied, namely analyzing the development of cultural heritage tourism destinations in Bayan village for sustainable tourism. The data sources for this research consist of primary data sources, namely the main sources obtained directly from informants. Both through interviews with sources and through direct observation. From this research it can be seen that the regional government of North Lombok Regency has designated the Bayan Beleq Ancient Mosque as a cultural tourist attraction with regional regulations and has implemented plans and activities to develop facilities and infrastructure, workforce and tourism. Development activities achieved include the construction of gates and public toilets at the Bayan Beleq Ancient Mosque, restoration of traditional houses, community development through education, skills training and tourism promotion through various sources.